The defense lawyer : [large type] the Barry Slotnick story - Patterson, James, 1947-; Wallace, Benjamin, 1968- (Little, Brown and Company, 2021)
Bronx-native Bernard Slotnick's mantra was that everyone deserved a good defense. And he was the best defender out there. A bold strategist in the courtroom, and a doting husband and father of four at home, 'Liberty's Last Champion' proudly stood up for the unpopular and the controversial. Known for his sharp mind (and his sharp suits), Slotnick, anointed the best criminal lawyer in the United States by The American Lawyer, had a remarkable legal career capped by an extraordinary twelve-year winning streak. From negotiating Melania Trump's pre-nup to representing "the Dapper Don" John Gotti, from defending "Subway Vigilante" Bernhard Goetz to mediating Bette Midler's bathhouse contract, Slotnick's unparalleled acumen defined a profession, a city, and an era.